12.0k views
1 vote
Which pair shows equivalent expressions? 2 x + 10 = negative 2 (x minus 5) Negative 2 (x + 5) = 2 x minus 10 Negative 2 x minus 10 = negative 2 (x + 5) Negative 2 (x minus 5) = negative 2 x minus 10

User Mliu
by
5.1k points

2 Answers

4 votes

Answer:

C

Explanation:

I just took the test

User Avitex
by
4.6k points
4 votes

Answer:

C. –2x – 10 = –2(x + 5)

Explanation:

Clearer choices:

2x + 10 = –2(x – 5)

–2(x + 5) = 2x – 10

–2x – 10 = –2(x + 5)

–2(x – 5) = –2x – 10

All choices have either:

–2(x – 5) for A and D

or –2(x + 5) for B and C

Simplify these expressions by expanding with the distributive property. Multiply the outside term "–2" with each term inside the brackets.

–2(x – 5)

= (–2*x) – (–2*5) Multiply each term by the coefficient

= –2x – (–10) Simplify the double negative to a positive

= –2x + 10 Expanded expression

This is not the same answer in A and D. They are not correct.

–2(x + 5)

= (–2*x) + (–2*5) Multiply each term by the coefficient

= –2x + (–10) Adding a negative is the same as subtraction

= –2x – 10 Expanded expression

This is the same answer for option C.

Therefore "C" is the answer.

User Roy Kachouh
by
5.4k points